Insan Kamil at the Crossroads of Time: Transformative Islamic Education Model to Face Global Challenges - Muzaki, Iqbal Amar; Mustofa, Taufik; Ramdhani, Khalid; Abidin, Jaenal; Waluyo, Kasja Eki (Intelektual: Jurnal Pendidikan dan Studi Keislaman, 2025)
The concept of insan kamil represents the ideal of the perfect human in Islam, reflecting spiritual, intellectual, and moral excellence. In the context of a rapidly changing global landscape shaped by social, technological, and value-based transformations, Islamic education is required to respond through a transformative approach that is both relevant and sustainable. This study aims to systematically examine how the concept of insan kamil is formulated and implemented within a transformative Islamic education model to address contemporary demands. Employing a Systematic Literature Review (SLR) approach, the research analyzed twelve scholarly articles published within the past five years focusing on insan kamil, Islamic education, and educational transformation. The review identified four central themes: the theoretical conceptualization of insan kamil, the dynamics of transformative change in Islamic education, the educational responses to global challenges, and the integration of spiritual values with global competencies in educational design. The findings reveal that insan kamil serves not only as a normative ideal but also as an implementable framework for curriculum reform, learning strategies, and character development. The main contribution of this article lies in its conceptual synthesis, which bridges Sufi thought with contemporary educational practice, providing an epistemological foundation for the development of holistic, contextual, and transformative Islamic education policies in the global era.